Optimalidasi Investasi Dana Haji Era Pandemi Covid-19 - Dedi Junaedi; Muhammad Rizal Arsyad; Siti Chaerijah Aurijah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
View MyStat This study aims to explore the optimal choice of Hajj financial investment through analysis of the relationship between the prospects for gold investment, Islamic stocks and rice agribusiness investment with the dynamics of exchange rates, inflation, BI-rate, pandemic cases and differences in policies in handling the Covid-19 pandemic. The method used is a mixed method between qualitative descriptions and quantitative analysis. The data used are primary and secondary data from January to August 2020. The analysis technique used is multiple regression with summy pandemic policy variables. The result: investing in gold, investing in Islamic stocks and investing in rice agribusiness can become priority options for Hajj financial investments. The prospect of investing in gold is quite bright and is not statistically significantly affected by exchange rate fluctuations, inflation, BI-rate and the case of a pandemic. Sharia stock investment (ISSI and JII indices) has good prospects even though it is influenced by the dynamics of exchange rates, inflation, BI-rate and the Covid pandemic. Likewise, the investment in rice agribusiness is considered prospective considering its greater impact on farmers and national food availability. The analysis shows that gold investment and rice agribusiness investment have a positive correlation and tend to strengthen each other.